Pengaruh Suhu Aktifasi dan Konsentrasi Bahan Pengaktif (NaOH) Terhadap Kualitas Arang Aktif dari Kayu Sikkam (Bischofia javanica) - , JEPRI GREIVA M PURBA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research of activated carbon from bishop wood (B. javanica) was aimed for utilizing bishop wood in order to be processed into activated carbon, identifying the quality and characteristics of activated carbon from bishop wood, and identifying the interaction between activation temperature and concentration of NaOH towards the quality of activated carbon. The best quality of activated carbon would be used to improve the quality of well water. The research employed the completely randomized design which was made in a factorial manner with two factors, namely activation temperature (750oC, 800oC, and 850oC) and concentration of NaOH (1%, 1.25%, and 1.5%) with five replications respectively. The bishop wood (B. javanica) was carbonized by using an electrical retort at 400 oC for three hours. This research applied chemical and thermal activation. The quality of activated carbon was tested according to the Indonesian National Standard for the technical Standard Quality of Powdered Activated Carbon, SNI 06-3730-1995. The obtained data were analyzed by using analysis of variance (ANOVA). Moreover, they would be tested further if there were significant differences with the honestly significant difference (HSD). The characteristics of activated carbon from bishop wood (B. javanica) were as follows: yield was 55.91-63.09%, moisture content 2.84-4.93%, volatile matter 42.71-53.97%, ash content 4.65-5.46%, fixed carbon 41.39%-51.85%, iodine adsorption 912.49-1595.46mg/g, benzene adsorption 6.28-10.14%, and blue methylene adsorption 138.22-141.45mg/g, respectively. The best quality of activated carbon was obtained at the activation temperature of 800oC and 1% NaOH concentration and applied as a well water purifier in Kranggan, Galur, Kulon Progo, Yogyakarta. After the purification, the characteristics of well water were as follows: color (7.17 Pt-Co) decreased by 90.44%, turbidity (6.58 NTU) decreased by 84.43%, pH (7.93) increased by 16.62%, hardness (117.57mg/L) decreased by 21.74%, ferrum (Fe) content (0.19mg/L) decreased by 92.69%, and manganese (Mn) content (0.14mg/L) decreased by 53.33%, respectively. The result of the analysis indicates that the quality of well water has been improved and complied with the Water Quality Standards according to Decree of the Minister of Health Affairs of the Republic of Indonesia Number 416/Menkes/Per/IX/1990.